The Changes in Drainage Systems of Weihe Basin and Sanmenxia Basin Since Late Pliocene Give New Insights Into the Evolution of the Yellow River - Liu, Jin; Wang, Ping; Chen, Xingqiang; Shi, Wei; Song, Lijun; Hu, Jianmin (Frontiers in Earth Science, 2022)
The formation of the Yellow River involved draining of a series of ancestral local lakes along their course, substantially changing the regional, geomorphic, and paleoenvironmental evolution. However, the evolution of the Weihe-Sanmenxia Basin section of the Yellow River remains indistinct as previous studies regard the Weihe Basin and Sanmenxia Basin as one integral basin of the Late Cenozoic. Here, we present the detrital zircon age spectra from the Pliocene-Pleistocene Sanmen Formation to clarify the drainage system evolution of the two basins since the Late Pliocene. The results reveal that these two basins belonged to different drainage systems in the Late Pliocene, because no sediments from the marginal mountains of the Weihe Basin accumulated in the Sanmenxia Basin. At 2.8/2.6 Ma, the currents presented at the edge of the basins and transported the sediment of east Hua Mountain, into the Sanmenxia Basin, where it was deposited. This integration likely leads to a mismatch between the deposition and regional paleoclimate in previous studies. At 1.0 Ma, the Sanmenxia Gorge was traversed and the Yellow River finally formed, depositing Jinshaan Gorge sediment into the Sanmenxia Basin and lower reaches of the Yellow River.